Lok Sabha elections in Rajasthan: reasons behind BJP clean sweep and tread reversal in state's electoral politics - Pandey, Rajan (Social Science in Perspective)
While electoral trend in Rajasthan used to be that the winning party in assembly election used to triumph in upcoming Lok Sabha elections as well. BJP this time succeeded in reversing it. The people of Rajasthan voted quite differently in the assembly and national elections. While BJP remained under table on the national level, it failed to bridge the gaps at state level. If we see the results of recently concluded Maharashtra and Haryana assembly elections and compare them with this year$1 (Bs Lok Sabha elections pending in coming month continue to show this trend, this would mean a comeback of regional satraps, while also a one party dominance at national level. - Reproduceds
Keywords: Elections - Rajasthan